Kepemimpinan Visioner Kepala Sekolah Perempuan dalam Peningkatan Profesionalisme Tenaga Kependidikan - Sunardi, Sunardi; Munfarida, Isah; Munir, Nur (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
Visionary leadership plays a crucial role in enhancing the professionalism of educational staff within academic institutions. This study focuses on the visionary leadership strategies implemented by female school principals at SMA Primaganda Jombang and their impact on educational staff. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observations, and document analysis involving school principals, educational staff, and stakeholders. The findings indicate that the principal employs various strategies, including fostering a culture of innovation, enhancing staff competencies through training, adopting a collaborative leadership approach, mentoring and coaching, continuous performance evaluation, and providing incentives and rewards. These strategies have proven effective in increasing motivation, productivity, and staff loyalty toward the school’s vision. The study concludes that well-implemented visionary leadership can create a professional and adaptable work culture. Therefore, further support from the government and educational stakeholders is necessary to strengthen leadership development programmes for female school principals and provide sufficient resources to improve overall educational quality.